Influence of a cereal rye cover crop on the critical period for weed control in soybean. (3rd February 2023) - Kumari, Annu; Price, Andrew J.; Korres, Nicholas E.; Gamble, Audrey; Li, Steve
Abstract: Soybean is the world's most widely grown leguminous crop and is an important source of oil and protein for food and feed in addition to other industrial uses. However, herbicide-resistant and troublesome weed control challenges limit yield potential and threaten conservation tillage (CT) systems. Cover crops have been widely adopted as an integrated pest management component in CT systems to suppress weeds and maintain soybean yield potential. A 3-yr field experiment was conducted to estimate the influence of a cereal rye cover crop following CT on the critical period for weed control (CPWC) in soybean. The experiment was implemented in a split-plot design in which main plots as CT following cover crop (CT + CC), CT following winter fallow (CT + WF), and conventional tillage (CVT), and subplots were multiple durations of weed-free and weed interference. Results showed that the estimated CPWC of CT + CC and CT + WF treatments was 0 wk and >7 wk, respectively, in 2018. In 2019, the estimated CPWC was 0 wk, 5.0 wk, and 1.3 wk under CT + CC, CT + WF, and CVT treatments, respectively. In 2020, the estimated CPWC was 3.5 wk, >6.2 wk, and 0 wk under CT + CC, CT + WF, and CVT treatments, respectively. The presence of a cover crop delayed the CTWR and caused an early beginning of the CWFP compared with CT + WF treatment, and hence shortened the CPWC in 2018 and 2019. In conclusion, the CT + WF system did not reduce the weed competition and subsequent yield loss in soybean compared to the CT + CC system.